Interaksi Sosial Siswa dengan Kelompok Teman Sebaya di Sekolah dan Implikasinya terhadap Pelayanan BK - Melchioriyusni Melchioriyusni; Zikra Zikra; Azrul Said (Indonesian Institute for Counseling, Education and Therapy (IICET), 2013)
In social interaction students with clusters of their peers in school, occurring social interaction being diverse. Students who less mutual esteem between students the one with students others. Some students who less cooperation in school and only wan to win own. Research purposes this to describe social interaction students with clusters of their peers in school of cooperation, competition and conflict and implication to the public BK. Method research used research descriptive. Population totaled 494 people and samples about 83 students. Overall social interaction students with clusters of their peers in school in good